The Effect of Coaching Leadership Style Towards Motivational Factors among School Rugby Players (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
The purpose of this research is to examine the effect of coaching leadership style towards motivational factor among school rugby players. The sample selection was based on two top schools in rugby performance which are from Wilayah Persekutuan Kuala Lumpur and Selangor state respectively. The sample selection consisted of 62 school rugby players and purposive sampling was used. They were given an online questionnaire to complete as the primary instrument for gathering information about coaching leadership style and motivation factor. Leadership Scale for Sport - 15 Version (LSS-15) is the questionnaire used to identify coaching leadership style while Sport Motivation Scale-II (SMS-II) is the second questionnaire used to identify motivational factor. Statistical Package for Social Science (SPSS) version 26.0 was used to analyzed all data in this study. The mean of the data obtained was determined using descriptive analysis to identify the preferred coaching leadership style among school rugby players, actual coaches’ coaching leadership style and motivational factor among school rugby players. Spearman Correlation was carried out to study the relationship of coaching leadership style and motivational factors among school rugby players. The researcher found that there is a significant relationship between coaching leadership style and motivational factor among school rugby players.